Hubungan Pengetahuan dan Sikap Dengan Praktik Hygiene Sanitasi Penjamah Makanan di Kecamatan Kadugede Kabupaten Kuningan Tahun 2013 - Amalia, Icca Stella; Rohaeni, Eni; Muriawati, Deasy (Jurnal Ilmu Kesehatan Bhakti Husada: Health Sciences Journal, 2015)
The efforts hygiene food sanitation is essential to maintaining public health. Know of 57 places the management of food and beverage in the area Kadugede health center distric examined only 40 paces food management (70,17%) were eligible. It is still lower the target in 2012 of 71,00%. The purpose of this study was to determine relationship of knowledge and attitudes of food handlers with hygiene sanitation place the food in Sub District of Kadugede of Kuningan District. Type of research is correlation analytic study using cross-sectional design. Populations in this study are food handlers where the processing power available in the working area kadugede health center distric of KuninganDistrict the total is 57 peoples. Samples in this study were taken by using purposive sampling technique, the data collected is primary data bad secondary data, while data analysis is univariate and bivariat analyze to determine the relationship between the independent variable and dependent variables using spearman rank test. Bivariate analyze knowledge relationships with food handlers practice hygiene food sanitation management place with ?=0,043 and r=0,269, attitudes relationship with food handlers practice hygiene with food sanitation management places value ?=0,033 and r=0,283. There is correlation between knowledge and attitudes of food handlers with hygiene sanitation practice place the food in the working area management kadugede health center distric of Kuningan district or health center of Kuningan District. Expected that the increase attitudes and practices of food handlers hygiene food sanitation management space, either by kadugede health center distric of Kuningan district and health offices of Kuningan District in the form of courses or training hygiene food sanitation either training hygiene food sanitation have to developed is more optimal implementation hygiene sanitation practices management foods.